Effect of Acute Cold Exposure on Energy Metabolism and Activity of Brown Adipose Tissue in Humans: A Systematic Review and Meta-Analysis - Huo, Chuanyi; Song, Zikai; Yin, Jianli; Zhu, Ying; Miao, Xiaohan; Qian, Honghao; Wang, Jia; Ye, Lin; Zhou, Liting (Frontiers in Physiology, 2022)
Background: The benefit of cold exposure for humans against obesity has brought the energy metabolism and activity of brown adipose tissue (BAT) induced by cold into focus. But the results are inconsistent. This review is aimed to systematically explore the effect of cold exposure on the activity of BAT and energy metabolism in humans. Methods: We searched relevant papers that were published from 1990 to 2021 and were cited in PubMed Central, Web of science, Embase and Cochrane Library databases to conduct this systematic review and meta-analysis. Energy metabolism, BAT volume, BAT activity and non-esterified fatty acids (NEFA) data reported in eligible researches were extracted. Meta-analysis was applied to combine the mean difference or standard mean difference with their 95% confidence intervals (95%CI). RevMan 5.3 software was used for meta-analysis and evaluating the risk of bias. Stata was used for evaluating the publication bias. Results: Ten randomized controlled trials were included in meta-analysis. Compared with human exposed in room temperature at 24℃, the energy expenditure (EE) was increased after acute cold exposure at 16~19 ℃(Z=7.58, P<0.05, mean different=188.43kal/d, 95% CI=139.73–237.13); BAT volume（Z=2.62, P<0.05; standard mean different = 0.41, 95% CI=0.10–0.73); BAT activity (Z=2.05, P =0.04, standard mean difference=1.61, 95% CI= 0.07–3.14) and the intake of BAT NEFA (Z=2.85, P<0.05; standard mean different=0.53, 95% CI=0.17–0.90) also increased. Conclusion: Acute cold exposure could improve the energy expenditure and BAT activity in adults, which is beneficial for human against obesity.